Implementasi Pengembangan Kelembagaan dalam Meningkatkan Kualitas Sumber Daya Manusia melalui Program Probebaya di Kelurahan Mesjid Samarinda Seberang - Lisdawati Lisdawati; Kresnina Kresnina; Lilis Hariyana; Daryono Daryono (Jurnal Syntax Admiration, 2024)
The purpose of the pro risk program is In general, so that the problems faced by the community are handled more quickly, through the implementation of the Development and Empowerment Program it is expected to be on target and on time, improve community welfare, increase community participation in development. This study uses qualitative descriptive methods with primary and secondary data, as well as observation, interview, and documentation techniques. Research also shows that institutional training has a significant influence on human resource development. Institutional training programs in Samarinda have also helped in community empowerment, improving living standards, reducing inequality, and overcoming unemployment. Therefore, it is recommended that this program continue to be supported and developed to achieve sustainable development in the future. With the involvement of the Probebaya Program in improving the quality of Human Resource Improvement, it can be considered a positive value and make the Probebaya Program have a function and role in Institutional Improvement.